Theoretical studies guaranties of constitutional rights and freedoms of servicemen in Ukraine - Шамрай, Богдан Миколайович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article examines the theoretical aspects of guarantees of constitutional rights and freedoms ofservicemen in Ukraine. Concepts of scientists views is reflected in relation to the question of guarantees ofrights and freedoms of man and citizen.